1998
DOI: 10.1046/j.1440-1770.1998.00074.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the nutrient status of two reservoirs in southeast Ghana

Abstract: The nutrient status of Weija and Kpong reservoirs, southeast Ghana, was assessed by determining seasonal indices and interannual changes. The nutrient levels were found to be higher in Weija Reservoir. However, ammonia did not follow that pattern. Seasonal distribution of nutrients also showed higher levels in Weija than in Kpong. Seasonal variation showed higher levels of nitrates in the rainy season at Weija than at Kpong; however, data from Kpong Reservoir involved considerable experimental error. The month… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 2 publications
0
9
0
Order By: Relevance
“…Ansa-Asare and Asante (1998) reported that there is a general decrease in the nutrient concentration in the dry season. Of all the nutrients, sulphate had very high concentration followed by phosphate in all the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Ansa-Asare and Asante (1998) reported that there is a general decrease in the nutrient concentration in the dry season. Of all the nutrients, sulphate had very high concentration followed by phosphate in all the samples.…”
Section: Resultsmentioning
confidence: 99%
“…Climatic conditions are tropical with wet season having moderate rainfall which peak in June and September with dry season spanning between December and March. Previous reports on Weija Reservoir include its physico-chemical characteristics, fish composition, fisheries and socio-economic status (Ameka et al, 2000;Ansa-Asare & Asante, 1998;Dassah & Abban, 1979;Abban, 1979;Balarin, 1988;…”
Section: Study Areamentioning
confidence: 99%
“…It was constructed in 1981 on the Volta River system mainly to provide hydroelectricity to supplement power generated from the Volta River dam. It has a total surface area of 38 km 2 , maximal depth of 15 m with a mean depth of 5 m, and a mean annual flow 1183 m 3 s -1 (Ansa-Asare and Ansong- 94 Asante, 1998;Quarcoopome et al, 2011). The Kpong Reservoir apart from power generation is also used for drinking water production, irrigation, recreation and also well known for its fisheries, especially the tilapias.…”
Section: Study Areamentioning
confidence: 99%
“…1). It has a surface area of about 38 km 2 , a mean depth of 5 m and a mean annual flow of 54.2 m 3 s -1 (AnsaAsare and Ansong- Asante, 1998, Asante et al, 2008. The Weija Reservoir was built in 1977 on the Densu River system.…”
Section: Study Areamentioning
confidence: 99%